Neutrophilic urticarial dermatosis as a presenting feature of systemic juvenile idiopathic arthritis. Issue 3 (25th March 2018) - Stringer, Thomas; Gittler, Julia; Meehan, Shane; Kahn, Philip; Oza, Vikash S.
Abstract: This report describes a case of chronic neutrophilic urticarial dermatosis as a presenting feature of systemic juvenile idiopathic arthritis. When encountered in children, neutrophilic urticarial dermatosis should raise suspicion of autoimmune or autoinflammatory disease.